Comparison of Two Creatinine-Based Estimating Equations in Predicting All-Cause and Cardiovascular Mortality in Patients With Type 2 Diabetes - Targher, Giovanni (American Diabetes Association, 2012)
OBJECTIVE: To compare the performance of two glomerular filtration rate (GFR)-estimating equations in predicting the risk of all-cause and cardiovascular mortality in type 2 diabetic patients. RESEARCH DESIGN AND METHODS: We followed 2,823 type 2 diabetic outpatients for a period of 6 years for the occurrence of all-cause and cardiovascular mortality. GFR was estimated using the four-variable Modification of Diet in Renal Disease (MDRD) study equation and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. RESULTS: At baseline, an estimated GFR (eGFR) <60 mL/min/1.73 m(2) was present in 22.0 and 20.2% of patients using the MDRD study equation and the CKD-EPI equation, respectively. A total of 309 patients died during the follow-up (152 patients from cardiovascular causes). Both creatinine-based equations were associated with an increased risk of all-cause and cardiovascular mortality. However, the CKD-EPI equation provided a more accurate risk prediction of mortality than the MDRD study equation. Receiving operating characteristic curves showed that the areas under the curve (AUCs) for all-cause mortality (AUC 0.712 [95% CI 0.682–0.741]) and cardiovascular mortality (0.771 [0.734–0.808]) using eGFR(CKD-EPI) were significantly greater (P < 0.0001 by the z statistic) than those obtained by using eGFR(MDRD) (0.679 [0.647–0.711] for all-cause mortality and 0.739 [0.698–0.783] for cardiovascular mortality). CONCLUSIONS: Our findings suggest that the estimation of GFR using the CKD-EPI equation more appropriately stratifies patients with type 2 diabetes according to the risk of all-cause and cardiovascular mortality compared with the MDRD study equation.